Recent advances on carbon dioxide capture through a hydrate-based gas separation process - Sabil, K.M. (Elsevier B.V., 2018)
Hydrate Based Gas Separation (HBGS) process is gaining interest globally as a greener solution for separation of CO2 from gaseous streams. In this paper, recently published articles on the development of HBGS process as a technique for separation of CO2 from flue gas, feed gas and high CO2 natural gas streams are briefly reviewed. Â© 2018 Elsevier B.V.